Potential for the development of light therapies in mild traumatic brain injury - Adam C Raikes; William DS Killgore (Concussion)
Light affects almost all aspects of human physiological functioning, including circadian rhythms, sleep–wake regulation, alertness, cognition and mood. We review the existing relevant literature on...